Intraspinal Plasticity Associated With the Development of Autonomic Dysreflexia After Complete Spinal Cord Injury - Michael, Felicia M.; Patel, Samir P.; Rabchevsky, Alexander G. (Frontiers in Cellular Neuroscience, 2019)
Traumatic spinal cord injury (SCI) leads to disruption of sensory, motor and autonomic function, and triggers structural, physiological and biochemical changes that cause reorganization of existing circuits that affect functional recovery. Propriospinal neurons (PN) appear to be very plastic within the inhibitory microenvironment of the injured spinal cord by forming compensatory circuits that aid in relaying information across the lesion site and, thus, are being investigated for their potential to promote locomotor recovery after experimental SCI. Yet the role of PN plasticity in autonomic dysfunction is not well characterized, notably with injuries at or above the sixth thoracic spinal cord segment which segregates critical spinal sympathetic neurons from supraspinal modulation that result in a syndrome termed autonomic dysreflexia (AD). This condition is typically defined as episodic hypertension and concomitant baroreflex-mediated bradycardia initiated by unmodulated sympathetic reflexes in the decentralized thoracolumbar spinal cord, and it is often triggered by noxious yet unperceived stimuli below the injury level and, if severe enough, requires immediate medical attention to reduce blood pressure. AD is frequently triggered by pelvic visceral distension (bowel and bladder), and there are documented structural relationships between injury-induced sprouting of pelvic visceral afferent C-fibers and excitation of lumbosacral PN that, in turn, sprout and relay noxious visceral sensory stimuli to rostral disinhibited thoracic sympathetic preganglionic neurons (SPN) that manifest hypertension. Herein, we review evidence for maladaptive plasticity of PN in neural circuits mediating heightened sympathetic reflexes after complete high thoracic SCI that manifest cardiovascular dysfunction, as well as contemporary research methodologies being employed to unveil the precise contribution of PN plasticity to the pathophysiology underlying AD development.